Structural Equation Model of Mathematics Anxiety and Self-Regulated Learning on Mathematical Literacy - Aziz Muhtasyam; Syamsuri Syamsuri; Cecep Anwar Hadi Firdos Santosa (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Establishing the significance of the relationship between latent variables in hypotheses that have been shown to have an impact was the goal of this investigation. This study looked at the connection between high school students' self-regulated learning, mathematical literacy, and mathematics anxiety. Pandeglang Regency high school students made up the study's demographic, and the sampling technique, which included 392 participants, was carried out utilizing the Slovin algorithm in terms of accreditation. This study focuses on mathematics anxiety and self-regulated learning. A self-regulated learning questionnaire, a mathematics anxiety survey, and a mathematical literacy exam serve as the study's tools. Additionally, structural equation modeling (SEM) will be used to examine the data gathered for this investigation. The results of this investigation show that: 1) High school students' mathematical literacy skills are negatively and significantly impacted by mathematics anxiety; 2) high school students' mathematical literacy skills are positively and significantly impacted by self-regulated learning; and 3) there is a significant negative correlation between high school students' mathematical literacy skills and mathematics anxiety. It is necessary to encourage kids' self-regulated learning and alleviate their arithmetic anxiety in order to enhance their mathematical literacy.